1999
DOI: 10.1021/jf980876d
|View full text |Cite
|
Sign up to set email alerts
|

Aging, Free Radicals, and Antioxidants in Wheat Seeds

Abstract: Free radical oxidative attack is considered a major cause of disruption and deteriorative changes observed in aged seeds. Antioxidant defense mechanisms may remove potentially damaging molecular species, and carotenoids may act as radical scavengers. The content of lutein, the major carotenoid in wheat seeds, was determined in the flours. It showed a rapid decrease during seed aging. In addition, the content of free radicals in glutens made from flours of wheat seeds after long-term storage was studied. The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
73
1
5

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(90 citation statements)
references
References 29 publications
11
73
1
5
Order By: Relevance
“…Carotenoid production in the seeds is a determinant for ABA production and seed dormancy (Taylor & Ramsay, 2005). In wheat grains, carotenoids are important antioxidants that limit the levels of free radicals and reduce the activities of degradative enzymes, thus avoiding the ageing of seeds (Pinzino, Nanni, & Zandomeneghi, 1999). Carotenoids protect the seed from deterioration and thereby contribute to a successful germination process.…”
Section: Introductionmentioning
confidence: 99%
“…Carotenoid production in the seeds is a determinant for ABA production and seed dormancy (Taylor & Ramsay, 2005). In wheat grains, carotenoids are important antioxidants that limit the levels of free radicals and reduce the activities of degradative enzymes, thus avoiding the ageing of seeds (Pinzino, Nanni, & Zandomeneghi, 1999). Carotenoids protect the seed from deterioration and thereby contribute to a successful germination process.…”
Section: Introductionmentioning
confidence: 99%
“…When correlating it to the antioxidant properties of lutein, which helps fight the seed aging fighting free radicals and reactive oxygen species, leading to consequent reduction of this compound in the seed (Pinzino et al, 1999). Thus, it is suggested that lutein is the main carotenoid acting as an antioxidant after the physiological maturation of the grain.…”
Section: Resultsmentioning
confidence: 99%
“…[4]. When its level exceeds the body's natural ability to deal with the potentially cytotoxic species, various pathological situations such as cancer, stroke, neurodegeneration, and aging may result [5][6][7][8][9]. In plants, O 2 Á-is commonly generated under illumination of chloroplasts by the occasional transfer of an electron from an excited Chl molecule or photosystem I component, under conditions of high NADPH/NADP ratios, to molecular O 2 [10].…”
Section: Introductionmentioning
confidence: 99%